Hematology and Plasma Biochemistry Reference Values of the Subgenus Hapturosaurus (Varanus macraei, Varanus prasinus, Varanus beccarii) Under Human Care - Jorge Sobrino-Yacobi; Manuel Fuertes-Recuero; Manuel de la Riva-Fraga; Teresa Encinas Cerezo; Andrés Montesinos Barceló; Álvaro Camina Vega; Pablo Morón-Elorza (Veterinary Sciences)
The tree monitor lizards of the subgenus Hapturosaurus are an understudied but increasingly important group of reptiles in zoos. The routine blood analysis of reptiles in captivity is highly recommended; however, the lack of reliable reference values for many species severely limits their clinical use. This study aims to establish preliminary reference values (RV) for the main hematological and biochemical parameters in three species of the subgenus Hapturosaurus (Varanus macraei, Varanus prasinus and Varanus beccarii). Blood samples were taken from healthy adult individuals (n = 34), females (n = 18) and males (n = 16), maintained under controlled conditions in a zoo. A complete biochemical analysis was performed on all individuals, including alanine-aminotransferase, alkaline phosphatase, gamma-glutamyl transpeptidase, aspartate-aminotransferase, creatine kinase, bile acids, urea, uric acid, total solids, total proteins, albumin, glucose, fructosamine, lactate, cholesterol, triglycerides, amylase, calcium, phosphorus, calcium:phosphorus ratio, and magnesium. In addition, a complete hematological analysis was conducted on these individuals, including hematocrit, hemoglobin concentration, total erythrocyte and leukocyte counts, and leukocyte differential count. From the data obtained, reference intervals were established following the guidelines provided by the American Society for Veterinary Clinical Pathology (ASVCP). In this study, the results of the three species were unified to increase the sample size and to obtain more representative reference intervals. This unification was supported by a statistical analysis using the one-factor ANOVA test, which showed no statistically significant differences between species (p < 0.050). These data constitute an essential first step for the clinical practice and management of these Hapturosaurus species in zoos and specialized centers. Future collaboration with other institutions will help expand the dataset and enhance the accuracy of the established reference values.